UTSMAN BIN AFFAN: ISU NEPOTISME DAN MUNCULNYA PEMBERONTAKAN - Arya Ficky Nugroho; Amril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to analyze the issue of nepotism during the reign of Caliph Uthman bin Affan and its impact on the emergence of rebellion. The research uses a literature study method with the source of classical and modern Islamic history literature. The results of the study show that the appointment of Uthman's relatives to strategic positions led to accusations of nepotism even though some historians consider the appointment to be based on loyalty and competence. This policy, coupled with weak supervision and slander spread by certain groups, triggered public dissatisfaction that led to the revolt and killing of Uthman. In conclusion, the issue of nepotism in Uthman's era needs to be viewed objectively by considering the socio-political context and broad governmental challenges at that time.